2019
DOI: 10.1021/acs.iecr.9b00324
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Efficient Reactive Dividing Wall Column for Simultaneous Esterification of n-Amyl Alcohol and n-Hexanol

Abstract: This study reports significant energy savings of combined reaction and distillation in a single reactive dividing wall column (RDWC) for the concurrent production of pure n-amyl and nhexyl esters, which are the stable node (SN) in each phase diagram of the quaternary reaction system. The continuous removal of the byproduct, water, from the unstable node (UN) azeotrope by L-L decantation drives the two esterifications in the forward direction and enables the production of the pure ester products. A vapor recomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…n -Butyl acetate (BuAC), n -amyl acetate (AmAC), and n -hexyl acetate (HexAC) were produced from the esterification of n -butanol (BuOH), n -amyl alcohol (AmOH), and n -hexyl alcohol (HexOH) with an acid ion-exchange catalyst, respectively. These reactions occurred in the liquid phase, and the reaction kinetic data was taken from prior studies, ,,, as shown below in eqs –. While the reaction rate is described by the activity for both n -hexyl and n -butyl esterification, the n -amyl esterification rate is expressed by the concentration.…”
Section: Kinetic Model and Thermodynamic Propertiesmentioning
confidence: 99%
See 3 more Smart Citations
“…n -Butyl acetate (BuAC), n -amyl acetate (AmAC), and n -hexyl acetate (HexAC) were produced from the esterification of n -butanol (BuOH), n -amyl alcohol (AmOH), and n -hexyl alcohol (HexOH) with an acid ion-exchange catalyst, respectively. These reactions occurred in the liquid phase, and the reaction kinetic data was taken from prior studies, ,,, as shown below in eqs –. While the reaction rate is described by the activity for both n -hexyl and n -butyl esterification, the n -amyl esterification rate is expressed by the concentration.…”
Section: Kinetic Model and Thermodynamic Propertiesmentioning
confidence: 99%
“…Our previous study, as shown in Figure b, proposed an indirect sequence for the simultaneous production of pure AmAC and HexAC esters, and it demonstrated that the sequence was possible but its energy consumption was much higher than the direct sequence in Figure a. Because the indirect sequence of the two esters, AmAC and BuAC, cannot produce the 99 mol % esters simultaneously ( x BuAC = 0.98 in Figure a) even with a high energy consumption, the indirect sequence of the triple esterification is infeasible to produce the three pure esters without sacrificing the enormous energy cost as described in the following section.…”
Section: Feasibility Of Multiple Esterification Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Heat integration techniques for recovering heat between separation units or between rectifying and stripping sections of the column are classified into external and internal heat integration. , The external heat integration regards an overhead vapor stream as a heat source and a bottom liquid stream as a heat sink. , As an example, a vapor recompression heat pump (VRHP), which can reduce the reboiler duty of the column, pressurizes the overhead vapor stream, and the compressed vapor is used to boil the bottom liquid. In the case of an internally heat-integrated distillation column (HIDiC), the vapor stream in the rectifying section provides latent heat to the liquid stream in the stripping section and can reduce the external reboil . External and internal heat integration, which are usually combined for improvement of the energy efficiency and economic performance, complement their own limitations such as complexities of the equipment design and difficulties of the system operation. , In the HIDiC proposed in an earlier study, all trays in the stripping and rectifying sections are thermally coupled using heat exchangers, and a VRHP is employed for additional energy recovery and pressure drop for stream connections.…”
Section: Introductionmentioning
confidence: 99%